Punishment Awaits: Criminal Liability for Producers and Distributors of Adulterated Alcoholic Beverages - Fernanda Lucky; Yogi Prasetyo; Aries Isnandar (Fakultas Syariah IAIN Langsa, 2026)
Ideally, the criminal justice system should provide maximum protection to society through effective law enforcement against producers and distributors of adulterated alcoholic beverages. In reality, however, the circulation of adulterated liquor continues to persist and recur, frequently resulting in fatalities due to weak regulatory oversight, complexities in criminal proof, and the suboptimal enforcement of criminal sanctions. This study aims to examine the criminal liability of producers and distributors of adulterated alcoholic beverages, the evidentiary framework for prosecuting such offenses, and the optimization of law enforcement as a preventive strategy within the Indonesian positive legal system. This research employs a qualitative library research design using a normative legal approach through the statute approach, conceptual approach, and case approach. The findings reveal that criminal liability may be imposed under the Indonesian Criminal Code, the Health Law, and the Consumer Protection Law, with evidentiary standards emphasizing mens rea, causal relationship, and scientific evidence.